2007
DOI: 10.1007/s10653-006-9069-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental radon studies in Mexico

Abstract: Radon has been determined in soil, groundwater, and air in Mexico, both indoors and outdoors, as part of geophysical studies and to estimate effective doses as a result of radon exposure. Detection of radon has mainly been performed with solid-state nuclear track detectors (SSNTD) and, occasionally, with active detection devices based on silicon detectors or ionization chambers. The liquid scintillation technique, also, has been used for determination of radon in groundwater. The adjusted geometric mean indoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 40 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…This detection of radon has mainly been performed with solid-state nuclear track detectors (SSNTD) and with active detection devices based on silicon detectors or ionization chambers [48, 49]. …”
Section: Discussionmentioning
confidence: 99%
“…This detection of radon has mainly been performed with solid-state nuclear track detectors (SSNTD) and with active detection devices based on silicon detectors or ionization chambers [48, 49]. …”
Section: Discussionmentioning
confidence: 99%
“…A major study of 100 public water supply systems in China showed a range from 0.04 to 100 Bq/l radon (Ren et al 1996). In Mexico groundwaters and water supplies are commonly around 2.2 Bq/l radon but can reach a maximum of 34.2 Bq/l radon (Segovia et al 2007).…”
Section: Background Radonmentioning
confidence: 99%
“…Global summary of indoor radon ( 222 Rn) activities (Bq/m 3 ) (UNSCEAR 2000), including additional Mexican data fromSegovia et al (2007) and Paarl, South African data fromLindsay et al (2008) …”
mentioning
confidence: 99%
“…In hal ing of in door ra don and its prog eny forms about 60 % of the to tal back ground ra di a tion dose of hu man be ings [7]. Ra don con cen tra tion in in door air is on av er age 2-10 times higher than that in the free atmo sphere [8][9][10] and it de pends on the rate of ex ha lation of ra don from the soil and the in ten sity of tur bulent air mix ing.…”
Section: Introductionmentioning
confidence: 99%